Social support utilization’s effect on post-traumatic stress symptoms: a Danish cross-sectional study of 383 ambulance personnel - Melander, Pernille; Vang, Maria Louison; Lindekilde, Nanna; Andersen, Lars Peter Sønderbo; Elklit, Ask; Pihl-Thingvad, Jesper (Frontiers in Psychiatry, 2024)
Introduction Social support is considered an important factor in prevention of mental illness. However, little is known about the association between ambulance personnel’s use of multiple types of social support and post-traumatic stress symptoms (PTSS). This study aims to assess if number of used social support types predicts PTSS for ambulance personnel. Apart from assessing the main effect of social support utilization, we were interested in investigating if social support utilization moderated the effect of frequency of critical events on PTSS. Materials and methods A total of 383 ambulance personnel completed a survey consisting of validated questionnaires. Hierarchical multiple linear regression analyses were performed to assess the association between frequency of traumatic exposure and utilization of social support and PTSS as outcome variable. Results Higher number of utilized social support types was associated with higher levels of PTSS (β = 0.15, p <.001). When serving as a moderator of the association between frequency of exposure to critical incidents and PTSS, social support utilization had a significant and positive interaction effect (β = 0.26, p = .049). 307 participants had used 2 or 3 types of informal support during the past year, whereas 81 had used 2 or 3 types of formal support. Conclusion To our knowledge, this is the first study investigating the relationship between utilization of multiple, concurrent social support types and PTSS. This study suggests that to understand the effects of social support among ambulance personnel, it is necessary to assess the utilization of multiple concurrent support types, contributing factors to social support use, and different patterns of social support utilization that constitutes professional life in ambulance work.